Museum of Desires - Kraus, Karola (Berlin : Distanz, 2011)
Giacometti, Alberto ; Picasso, Pablo ; Derain, André ; de Kooning, Willem ; Baselitz, Georg ; Lassnig, Maria ; Picabia, Francis ; Bacon, Francis ; Roth, Dieter ; Schad, Christian, et al.
This publication is published on the occasion of the exhibition Museum of Desires at Museum Moderner Kunst Stiftung Ludwig Wien, September 10, 2011 - January 8, 2012)
boek